Training on Developing Powtoon-Based Animated Video Learning Media for Mathematics Practitioners in Mataram - Ratna Yulis Tyaningsih; Arjudin Arjudin; Nilza Humaira Salsabila; Xie Guilin (Yayasan Adra Karima Hubbi, 2023)
Background. Learning media has a very important role in supporting the acceptance of information conveyed by the teacher to students. Through the media, information will be more easily accepted by students because it looks attractive so that students can focus more on understanding the material. However, based on initial observations in the field, many teachers have not utilized the latest digital media such as Powtoon. Purpose. The media that are commonly used are still in the form of Powerpoint (Ppt) and Student Worksheets. Method. This Community Service Activity (PKM) aims to provide training and assistance in making Powtoon-based animated video learning media for Mathematics academics in Mataram City. This activity was carried out online and was attended by 50 participants who were Mathematics practitioners in the City of Mataram. Results. The result of this community service activity is a Powtoon-based animated video learning media made by each participant. This learning media created is the result of mentoring PKM activities and is the output of these activities. In addition, there was a positive response from the trainees of 91.04% regarding mastery of the material, the technique of delivering the material, suitability of the material and the needs of the trainees, and the completeness and ease of operation of the Powtoon program. Conclusion. Thus, this PKM activity significantly improves the quality of learning mathematics in the classroom. Through this training and mentoring, trainees as Mathematics practitioners in the City of Mataram can produce Powtoon-based animated video learning media that suit students' needs.